Primary Splenic Pregnancy- A Rare but Imperative Cause of Hemoperitoneum - Case Report and Review of Literature - Ruchi RATHORE; .Shilpi; Ratna CHOPRA; Namrata NARGOTRA (Federation of Turkish Pathology Societies, 2019)
Primary splenic pregnancy is an extremely rare form of extratubal ectopic pregnancy. These cases often cause splenic rupture in very early course of their gestation thereby presenting with hemoperitoneum in emergencies. Owing to the higher risk of exsanguination and death caused by hemoperitoneum, it is essential to diagnose these cases for proper management and better prognosis of the patients. We present the case of a 23-year-old female, gravida 2, para 1, live issue 1 presenting to the emergency outpatient department with acute abdomen and hemoperitoneum. There was no history of trauma. The patient had a positive urine pregnancy test and raised beta HCG levels. Emergency laparotomy revealed an otherwise unremarkable fallopian tube and ovary with a hemoperitoneum of 2.5 liters. A tiny splenic laceration was considered to be the source of bleeding and splenectomy was performed. Microscopy was suggestive of a primary ectopic pregnancy, spleen. Since hemoperitoneum in pregnancy is a rare but potentially fatal condition with a high risk of mortality, an accurate preoperative diagnosis is crucial in the management of such patients. The possibility of a ruptured extratubal ectopic pregnancy must be considered as one of the differential diagnoses of acute abdomen with hemoperitoneum in women of childbearing age.